Middle East and North Africa Economic Developments and Prospects, September 2011 : Investing for Growth and Jobs - World Bank (Washington, DC, 2013)
The report highlights the important links between good governance on a level legal and regulatory playing field, and the ability of investment to stimulate growth. Investment in the Middle East and North Africa (MENA) region has been strong over the last two decades in comparison with Latin America and Eastern Europe. However, in the oil exporting countries, it has been primarily supported by large and expanding public investments. Oil importers, in contrast, have shown more strength in private investment, which has increased in recent years. A concern with reliance on public investment is that in economies with weak governance there is no evidence that public investment stimulates growth. In contrast, in countries with an adequate level of protection of property rights and legal institutions, public investment is strongly linked to growth. The report also makes a strong case for private investment in services and manufacturing as engines of job creation and income growth in the region.